El Excentrico, 1962-09-05 - Garcia, Humberto:::Publisher:::::::::::: (San Jose, California; Garcia Printing, 2023)
September 5, 1962 [5 de septiembre de 1962]. Ano 12, No 21, Cover has picture of San Jose City Manager Hamman and City Health Department Sanitarian Luis Juarez. The headline reads "San Jose Improvement week - September 15th thru 23rd."